2017
DOI: 10.1242/dev.143776
|View full text |Cite
|
Sign up to set email alerts
|

The Abl pathway bifurcates to balance Enabled and Rac signaling in axon patterning in Drosophila

Abstract: The Abl tyrosine kinase signaling network controls cell migration, epithelial organization, axon patterning and other aspects of development. Although individual components are known, the relationships among them remain unresolved. We now use FRET measurements of pathway activity, analysis of protein localization and genetic epistasis to dissect the structure of this network in Drosophila. We find that the adaptor protein Disabled stimulates Abl kinase activity. Abl suppresses the actin-regulatory factor Enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…24,33 For some time, the role of Dab in Abl signaling was controversial, although several studies have now convincingly established the central role of Dab in the Abl network. 27,34,35 Dab interacts synergistically with Abl and trio mutations and antagonistically to ena, demonstrating that Dab is a positive component of the Abl pathway, and Dab protein co-immunoprecipitates with Abl. In addition, it was found that Dab regulates Abl localization in the retinal neuroepithelium and embryonic epithelia of Drosophila, suggesting it may be upstream of Abl.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…24,33 For some time, the role of Dab in Abl signaling was controversial, although several studies have now convincingly established the central role of Dab in the Abl network. 27,34,35 Dab interacts synergistically with Abl and trio mutations and antagonistically to ena, demonstrating that Dab is a positive component of the Abl pathway, and Dab protein co-immunoprecipitates with Abl. In addition, it was found that Dab regulates Abl localization in the retinal neuroepithelium and embryonic epithelia of Drosophila, suggesting it may be upstream of Abl.…”
Section: Introductionmentioning
confidence: 99%
“…This makes immediate readouts of pathway activity essential for drawing reliable conclusions. 27 Finally, the dynamic processes in the cytoskeleton are typically not linear pathways; instead they are cyclical. Manipulations that simply lock a piece of the machine into an ON or OFF state generally are not an effective way to study the mechanism of the cycle phenotypically since either condition just breaks the cycle.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations